Lysimeter validation based on physicochemical characterisation of leachate from municipal solid waste in a tropical region. (10th April 2019) - Manzatto, Mariana Politti; Miguel, Miriam Gonçalves
Leachates produced by municipal solid waste (MSW) in the city of Campinas, Southeastern Brazil, were confined - either to three lysimeters (models), or to an experimental cell built in the municipal sanitary landfill - and analysed. The leachates were characterised weekly through physicochemical variables. Monitoring time was 520 days. Statistical analyses were performed to validate the models as a means of studying real-scale landfills. Data was obtained from detailed monitoring of the MSW's biodegradation process, enabling the identification of transitional periods. The transition from the acidogenic phase to the methanogenic phase occurred between 100 and 150 days in the experimental cell, and between 120 and 230 days in the models. Use of lysimeters to determine biodegradation phases in tropical regions was validated only for leachates' chemical oxygen demand (COD) and volatile fatty acids (VFA) variables.